Impact of Bad Banking Debts on Profitability (Global Journal of Management and Business Research, 2023)
The study aimed to demonstrate the effect of size for bad debts on the rate of return on assets for the Jordanian banking sector a case study 2010-2022 the sample of the study is the Jordanian banking sector this study relied on the descriptive and analytical approach The study concluded that there is no effect of size for bad debts on the rate of return on the results The study recommended the necessity of providing the necessary competencies and expertise to adopt new standards and decisions and move towards possessing the technical capabilities that enable the supervisory authorities to measure risks through the methods stipulated in the international Basel standards in addition to Providing data and information that facilitate accurate evaluation of what banks are doing
Keywords: size of bad debt; return on assets